Sources of Western Zhou history : inscribed bronze vessels - Shaughnessy, Edward L., 1952- (University of California Press, 1991)
The thousands of ritual bronze vessels discovered by China's archaeologists serve as the major documentary source for the Western Zhou dynasty (1045-771 B.C.). These vessels contain long inscriptions full of detail on subjects as diverse as the military history of the period, the bureaucratic structure of the royal court, and lawsuits among the gentry. Moreover, being cast in bronze, the inscriptions preserve exactly the contemporary script and language. This text provides historiography and interpretation of these objects. By demonstrating how the inscriptions are read and interpreted, the author makes accessible in English some of the most important evidence about life in ancient China.